European and international principles for quality management in education using intelligent technologies - Ivanyshyn, Alla (Видавництво Львівської політехніки, 2023)
The article compares the international and European requirements for institutions of higher education. General international principles of quality management were also considered and adapted to institutions of higher education. The main requirements for the quality management system (QMS) of a higher education institution (HEI) following international and European standards) as well as the advantages and main requirements for the implementation of the quality management of educational services, as a tool for managing the processes of providing educational services and improving their quality.
Keywords: Quality Management System (QMS); Institution of Higher Education; Educational Services; Intelligent System